Dechema chemistry data series vapor liquid equilibrium data collection - Gmehling, J.; U. Onken; W. Arlt. (Frankfurt Dechema, 1983)
part. 6c. Aliphatic hydrocarbons (supplement 1)
part 6c supplement 1
Keywords: Vapor liquid equilibrium -- Tables